Videogrammetry Technique For Arm Positioning Of Bio-Production Robot - Razali, Mohd Hudzari (2002)
This thesis describes the development of the 'robot eye' system for agriculture robot to predict actual distance of the target object. Videogrammetry technique and triangulation method were used to measure distance of the target object. By 'clicking' on the image displayed on the user interface, the 3-dimensional (3D) distance of the target from robot arm will be generated and sending a signal to the robot to grip the selected target. The mathematical model of the robot arm applied real time simulation and was developed for use in the computing process. The 'robot eye' used WebCam digital cameras for 3D coordinate measurement that displayed the real environment in the user interface that was created using Visual Basic Version 6. The robot tool was designed, built and modified for this project using computer control and pneumatic drive system. The emphasis of the fabrication was to emulate the function of picking and harvesting of agricultural products. Robot communication was developed using ICP- DAS I/O modules that remotely sense up to a distance of 100 meters. This conceptual project is suitable for further research on 'robot eye' development using the non-contact measurement of 3D coordinate detection of the target object in real time mode.